The Effectiveness Of Using Show And Tell (S&T) Method To Teach Vocabulary : A Pre-Experimental Study At Class VIII-A In SMPN 1 Diwek In The Academic Year Of 2022/2023 - Mulyani, Musyafa'ah Dewi; Maskhurin Fajarina (Politeknik Kampar, 2023)
The aim of this study was to find out whether the Show and Tell (S&T) Method is effective to teach vocabulary at class VIII-A in SMPN 1 Diwek. The research method of this study was quantitative method. Furthermore, the design of this study was pre-experimental design. This study used test as the instrument, the tests are pre-test and pots-test which consist of 20 questions. The mean score of post-tests showed a higher score than the mean score od pre-test. The mean score of pre-tests was 68,59 while the mean score of post-tests was 8359. The data analysis using t-test on SPSS 25.0 showed that the t count (7.820) is greater than the t table (2.042) and the sig. (2-tailed) 0.000 is smaller than the significant level of 0.05 (5%). Thus, it can be concluded that there was a significant difference between the students’ vocabulary mastery before and after the Show and Tell (S&T) Method was applied. This means that the method is effective to teach vocabulary at class VIII-A in SMPN 1 Diwek.